Does Collateral Reduce Loan-Size Credit Rationing? Survey Evidence - Alemu Tulu Chala; Jens Forssbaeck (Lund University, School of Economics and Management, Department of Economics, 2018)
In theory, the use of collateral in credit contracting should mitigate the information problems that are widely held to be the primary cause of credit rationing. However, direct empirical evidence of the link between collateral use and credit rationing is scant. This paper examines the relationship between collateral and credit rationing using survey data that provides clean measures of quantity and loan size rationing. We find that selection problems arising from the loan application process and co-determination of loan terms significantly influence the link between collateral and rationing. Accounting for these problems, our results suggest that collateral reduces the likelihood of experiencing loan-size credit rationing by between 15 and 40 percentage points, and that collateral also decreases the relative loan amount rationed.
Keywords: D82; G21; G39; 330; Loan-Size rationing; Collateral; Small business; Information asymmetry